MASALAH KEMASYARAKATAN DAN PANDANGAN CHAIRUL HARUN DALAM NOVEL WARISAN - Djamari Djamari (Sawo Manila, 2010)
Novel Warisan describes about the social life in Minangkabau and presents social conflicts of its societies, especially about the family system in Minangkabau creatively presented by the author. By describing the conflicts in Minangkabau, particularly concerning about inheritance, marriage, and matrilineal system, therefore, there will be found the social life of those societies in this novel. In fact, nonfinancial inheritance is much more beneficial than the financial one.